Diagnostic and therapeutic recommendations in pancreatic ductal adenocarcinoma. Recommendations of the Working Group of the Polish Pancreatic Club - Winter, Katarzyna; Talar-Wojnarowska, Renata; Dąbrowski, Andrzej; Degowska, Małgorzata; Durlik, Marek; Gąsiorowska, Anita; Głuszek, Stanisław; Jurkowska, Grażyna; Kaczka, Aleksandra; Lampe, Paweł; Marek, Tomasz; Nasierowska-Guttmejer, Anna; et al. (Gastroenterology Review/Przegląd Gastroenterologiczny, 2019)
These recommendations refer to the current management in pancreatic ductal adenocarcinoma (PDAC), a neoplasia characterised by an aggressive course and extremely poor prognosis. The recommendations regard diagnosis, surgical, adjuvant and palliative treatment, with consideration given to endoscopic and surgical methods. A vast majority of the statements are based on data obtained in clinical studies and experts’ recommendations on PDAC management, including the following guidelines: International Association of Pancreatology/European Pancreatic Club (IAP/EPC), American Society of Clinical Oncology (ASCO), European Society for Medical Oncology (ESMO), National Comprehensive Cancer Network (NCCN) and Polish Society of Gastroenterology (PSG) and The National Institute for Health and Care Excellence (NICE). All recommendations were voted on by members of the Working Group of the Polish Pancreatic Club. Results of the voting and brief comments are provided with each recommendation.